Model of Household Industrial Business Development to Increase Family Income - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Currently small industry entrepreneurs should be able to prepare themselves and have good strategis in producing quality products and have a wide marketing network, so that the market or consumers can accept the products produced, so that small business industries can increase family income.